2000
DOI: 10.2486/indhealth.38.15
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Coronary Heart Disease in Japanese Taxi Drivers as Determined by Coronary Angiographic Analyses.

Abstract: Several epidemiological studies have shown that the prevalence of ischemic heart disease is higher in occupational drivers than in people with other occupations. Although occupation categories can be surrogate measures for coronary risk factors, the relationships between taxi driving and severity of coronary heart disease (CHD) has not been investigated. Even more important, the contribution of risk factors to the severity of CHD in taxi drivers remains unclear. Our study tested the hypothesis that taxi drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
2
36
2
1
Order By: Relevance
“…1,2 In a Japanese study, the prevalence of myocardial infarction and multi-vessel disease was higher among male taxi drivers than non-drivers. 3 In a Swedish study, drivers had higher rates of smoking, overweight, low physical activity, and job strain compared to men in the general population. 4 Elevated myocardial infarction risk remained after adjusting for these factors and for diabetes, hypertension, and socioeconomic group.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In a Japanese study, the prevalence of myocardial infarction and multi-vessel disease was higher among male taxi drivers than non-drivers. 3 In a Swedish study, drivers had higher rates of smoking, overweight, low physical activity, and job strain compared to men in the general population. 4 Elevated myocardial infarction risk remained after adjusting for these factors and for diabetes, hypertension, and socioeconomic group.…”
Section: Introductionmentioning
confidence: 99%
“…Various epidemiologic studies have revealed that the incidence (1)(2)(3)(4)(5) and hospitalization rate (6, 7) of cardiovascular disease are high, and taxi-driver patients are characterized by more extensive coronary atherosclerosis in association with a higher prevalence of diabetes mellitus and obesity than nontaxi-driver referents (8). In Japan, a notable number of taxi drivers is involved in karoshi (death from overwork) cases (9).…”
mentioning
confidence: 99%
“…Kurosaka et al reported a greater prevalence of obesity, diabetes, dyslipidemia, and habitual smoking among Japanese taxi drivers than in other occupational workers. 10) We believe that similar health status trends may increase the incidence of AAD among Japanese commercial dirivers. Regular health checkups and improvements in the work enviroment are important for prevention of aortic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that the prevalence of CAD is higher among occupational drivers than among persons of other occupations. 10) However, few previous studies have investigated whether a relationship exists between occupational driving and the development of aortic disease. Some specific sports activities, including weight lifting, can trigger the onset of AAD due to a rapid increase in hemodynamic stress.…”
Section: Discussionmentioning
confidence: 99%